Immunological Characterization of Acid Phosphatase in an Endophytic Fungus - Malla, Rajani; Zeyaullah, Md; Pokharel, Utprekshya; Varma, Ajit (Nepal Journal of Science and Technology, 2007)
Piriformospora indica produced only one form of intracellular acid phosphatase irrespective of the phosphate concentration and was purified. The enzyme was possibly a constitutive enzyme showing molecular mass of 66kDa as separated by SDS PAGE. Antibodies raised against cytosolic acid phosphatase of P. indica using gel band in native PAGE after selective precipitation of ammonium sulfate followed by gel filtration and ion exchange chromatography, gave productive antibody and immunoblotting analysis. Its reaction with native protein as well as denatured protein was significant. The antibody immunoprecipitated a single band of approximately 66kDa protein in SDS gel. The antibody localized the enzyme on the polyphosphate granules, cell-wall, vacuoles and cytoplasm of the mycelium indicating the possible sites of phosphate metabolism. Nepal Journal of Science and Technology Vol. 7, 2006